Konstruksi Kedisiplinan melalui Habituasi Kegiatan Keagamaan: Studi Kasus di SMP Al-Ikhlas Tarokan Kediri - Muhammad Muhlisin; Edi Nurhidin (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2020)
The low disciplinary behavior of students is one of the problems faced by many educational institutions. Even though discipline is the personality builder of the student. By practicing discipline, other good habits will come. Strengthening student discipline can be inserted through school activities or school culture according to the needs and conditions of the school. Therefore, this article describes the school culture in the form of istigasah activities to strengthen student discipline at SMP Al-Ikhlas Tarokan Kediri. This research uses a qualitative approach. The data collection was carried out using the interview method, observing, collecting and examining, and feeling. Data analysis used includes pattern matching, making explanations, and time series analysis. The results showed that the implementation of istigasah at SMP Al-Ikhlas Tarokan Kediri has been running well. However, some efforts are still needed so that these istigasah activities can be carried out consistently. Implemented methods include: implementing discipline, checking student notebooks, exemplary teachers, and using rewards and punishments.